Successful switch to rilpivirine/tenofovir/emtricitabine in HIV‐1‐infected patients with an isolated K103N mutation acquired during prior nonnucleoside reverse transcriptase inhibitor therapy. Issue 10 (16th April 2014) - Rokx, C; Verbon, A; Rijnders, BJA
Abstract : Objectives: Whether treatment‐experienced HIV‐1‐infected patients with an acquired K103N mutation after failing nonnucleoside reverse transcriptase inhibitor (NNRTI) regimens can be treated with rilpivirine is unknown. The aim of this pilot study was to evaluate the efficacy of rilpivirine/tenofovir/emtricitabine in HIV‐1‐infected patients with an isolated K103N mutation. Methods: A prospective study was carried out in HIV‐1‐infected adults who acquired the K103N mutation on failing NNRTI regimens. No other mutations in reverse transcriptase were allowed. Patients had to be on second‐line regimens with HIV‐1 RNA < 200 copies/mL for ≥ 6 months. Exclusion criteria were: use of acid‐reducing agents, insufficient caloric intake and impaired renal function. Of primary interest was virological success (HIV‐1 RNA < 200 copies/mL) at weeks 6, 12, 24 and 48. Results: Of 1550 HIV‐1‐infected patients at the Erasmus Medical Center Rotterdam, we identified 10 HIV‐1‐infected patients with an isolated K103N mutation acquired after NNRTI failure. Five patients were not eligible for inclusion in the study, and two patients refused participation. Three African women (23–35 years of age) were included and were switched from boosted protease inhibitor‐based second‐line therapies to rilpvirine/tenofovir/emtricitabine. HIV‐1 RNA was < 200 copies/mL at weeks 6, 12, 24 and 48 for all patients. No adverse events were observed. All patients had HIV‐1 RNA < 200 copies/mL for 6−50 months prior to the switch. Conclusions: This pilot study demonstrates the successful switch of HIV‐1‐infected patients who acquired an isolated K103N mutation during previous NNRTI therapy to rilpivirine/tenofovir/emtricitabine. In selected patients, single‐tablet regimens are also becoming a valid treatment option for second‐line HIV‐1 therapy.